Secure transmission for MIMO THz communication system - Sharma, Shubha (2024)
Terahertz (THz) band offers large accessible band-width and spatially confined beams for the realization of secure and high data rate communication. The paper aims to achieve security at THz band by considering a multiple-input-multiple-output (MIMO) wiretap channel. Source with M_A antennas transmits using transmit antenna selection (TAS) technique and both main user and eavesdropper equipped with respective M_M and M_W antennas receive using maximal ratio combining (MRC) technique. In order to assess the secrecy performance, statistical characteristics are derived for the proposed system. Based on the derived statistical characteristics, the exact closed-form expressions for lower bounds for secrecy outage probability and probability of strictly positive secrecy capacity are derived. Results show that the improvement is oserved in the secrecy performance, which is primarily attributed to the utilization of transmit diversity techniques. It is demonstrated that non-linearity of the channel and multi-paths can also be exploited to enhance the physical layer security.